Star Wars : the original trilogy stories - LUC; Rood, Brian; Lucas, George, 1944- (Glendale, Calif. : Disney/Lucasfilm Press, 2015)
A collection of eighteen stories about Han Solo, Luke Skywalker, and Princess Leia as they fight to end the rule of Darth Vader.
"Based on the story and screenplay by George Lucas."
2.2
K-3
Keywords: Space warfare -- Juvenile fiction; Life on other planets -- Juvenile fiction; Star Wars fiction; Space warfare -- Fiction; Life on other planets -- Fiction; Star Wars fiction; Space warfare -- Fiction; Life on other planets -- Fiction; Star Wars fiction; Movie novels; Science fiction